2014
DOI: 10.1557/jmr.2014.191
|View full text |Cite
|
Sign up to set email alerts
|

Thermophysical properties of SnO2-based transparent conductive films: Effect of dopant species and structure compared with In2O3-, ZnO-, and TiO2-based films

Abstract: We investigate the effect of dopant species and structure on the thermal conductivity of Sb-doped SnO 2 (ATO) and Ta ) and considerably larger than that for amorphous ATO films). These facts lead us to conclude that the base-material species (SnO 2 or In 2 O 3 ) and structure (polycrystalline or amorphous) affect the thermophysical properties of ATO and TTO much more than the dopant species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 39 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…Until recently, numerous primary and binary oxides were reported to display mobilities reaching sometimes well over 200 cm 2 V À1 s À1 . [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] In the second half of the last decade, many more promising new amorphous oxides were reported. Compared to earlier works, the composition of the materials became more complex, and mainly ternary oxides were reported on.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until recently, numerous primary and binary oxides were reported to display mobilities reaching sometimes well over 200 cm 2 V À1 s À1 . [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] In the second half of the last decade, many more promising new amorphous oxides were reported. Compared to earlier works, the composition of the materials became more complex, and mainly ternary oxides were reported on.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, numerous primary and binary oxides were reported to display mobilities reaching sometimes well over 200 cm 2 V −1 s −1 . 22–36…”
Section: Introductionmentioning
confidence: 99%
“…The 3D charge and 2D phonon transports contribute greatly to the relatively high power factor with extremely low thermal conductivity along the out-of-plane direction in SnSe. In addition, it was reported that Bi is also an effective n-type dopant in SnSe, and the carrier concentration can reach ~ 2.1 × 10 19 cm −3 at 773 K. [76] Compared with high-performance single crystals, polycrystalline SnSe, which has better mechanical properties and higher possibility to be used in devices, possesses much lower carrier mobility because of the strong scattering from the enormous grain boundaries. Theoretically, the thermal conductivity of polycrystal SnSe should be much lower than that of single crystal because of the extra scattering of phonons.…”
Section: Thermoelectricitymentioning
confidence: 99%
“…Heat diffusion through the Ni-Mg films was investigated using a time-domain thermoreflectance (TDTR) method. [10][11][12][13][14][15][16][17][18][19][20][21] The measurements were conducted in situ using a rear-heating/ rear-detection (RR) type picosecond pulsed light heating thermoreflectance apparatus. The 3-layered films of Pd/Ni-Mg/Mo were placed in a specially designed sealed chamber, where the measurements were performed under open air and N 2 -H 2 (H 2 : 3%) mixture gas atmospheres (see Fig.…”
mentioning
confidence: 99%
“…Similar approaches have been reported for various transparent conductive oxide films, such as Sn:In 2 O 3 , 16,17) Al:ZnO, 18) In-Ga-Zn-O, 19) Nb:TiO 2 , 20) and Sb:SnO 2 . 21) The thermal conductivities carried by free electrons, estimated through the WFL, are presented in Table II. The higher thermal conductivity in the metallic state is attributed to heat transfer facilitated by free electrons, while the significant decrease in thermal conductivity during hydrogenation is attributed to the absence of free electrons.…”
mentioning
confidence: 99%